Laminaria digitata phlorotannins decrease protein degradation and methanogenesis during in vitro ruminal fermentation. (14th February 2018) - Vissers, Anne M; Pellikaan, Wilbert F; Bouwhuis, Anouk; Vincken, Jean‐Paul; Gruppen, Harry; Hendriks, Wouter H
Abstract: BACKGROUND: Phlorotannins (PhTs) are marine tannins consisting of phloroglucinol subunits connected via carbon–carbon and ether linkages. These have non‐covalent protein binding properties and are, therefore, expected to be beneficial in protecting protein from hydrolysis during ruminal fermentation. In this study, the effectiveness of a methanolic PhTs extract from Laminaria digitata (10, 20, 40, 50, 75 and 100 g kg −1 tannin‐free grass silage, with or without addition of polyethylene glycol (PEG), was investigated in vitro on protection of dietary protein and reduction of methane (CH4 ) in ruminal fluid. RESULTS: Addition of PhTs had linear ( P < 0.0001) and quadratic ( P = 0.0003) effects on gas and CH4 production, respectively. Optimal dosage of PhTs was 40 g kg −1 as at this point CH4 decreased ( P < 0.0001) from 24.5 to 15.2 mL g −1 organic matter (OM), without affecting gas production ( P = 0.3115) and total volatile fatty acids ( P = 1.000). Ammonia trended ( P = 0.0903) to decrease from 0.49 to 0.39 mmol g −1 OM, indicating protection of protein. Addition of PEG inhibited the effect of tannins at all dosage levels, and none of the fermentation parameters differed from the control. CONCLUSION: PhTs effectively protected protein from fermentation and reduced ruminal methanogenesis. © 2017 Society of Chemical Industry